The Okanagan Charter: Evolution of Health Promotion in Canadian Higher Education - Squires, Vicki; London, Chad (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
Campuses have never had such an intense focus on health promotion as they do at present as we work toward a post-pan-demic future. This article examines the evolution of approaches from a student-centric focus to a systems approach, tracing the history of health promotion on Canadian campuses. Universities have evolved from the initial attempts at providing oversight over student behaviour, to the increased need for supports after the influx of World War II veterans, to the focus on providing a much broader range of supports from a holistic stance. The current context of a more intentional and organized approach to health promotion for students, faculty, and staff is explored; the shift includes adoption of the Okanagan Charter (2015) at many campuses. Lastly, the authors suggest future directions for campuses to take in addressing the current health issues and in supporting well-being on Canadian campuses now and in the future.